4(3x-3)=5-(3+4x)

Simple and best practice solution for 4(3x-3)=5-(3+4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x-3)=5-(3+4x) equation:


Simplifying
4(3x + -3) = 5 + -1(3 + 4x)

Reorder the terms:
4(-3 + 3x) = 5 + -1(3 + 4x)
(-3 * 4 + 3x * 4) = 5 + -1(3 + 4x)
(-12 + 12x) = 5 + -1(3 + 4x)
-12 + 12x = 5 + (3 * -1 + 4x * -1)
-12 + 12x = 5 + (-3 + -4x)

Combine like terms: 5 + -3 = 2
-12 + 12x = 2 + -4x

Solving
-12 + 12x = 2 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-12 + 12x + 4x = 2 + -4x + 4x

Combine like terms: 12x + 4x = 16x
-12 + 16x = 2 + -4x + 4x

Combine like terms: -4x + 4x = 0
-12 + 16x = 2 + 0
-12 + 16x = 2

Add '12' to each side of the equation.
-12 + 12 + 16x = 2 + 12

Combine like terms: -12 + 12 = 0
0 + 16x = 2 + 12
16x = 2 + 12

Combine like terms: 2 + 12 = 14
16x = 14

Divide each side by '16'.
x = 0.875

Simplifying
x = 0.875

See similar equations:

| 2x+5=-3-2 | | a/2-a^4/16 | | secx(1/acc(x))-3sinx=0 | | 10-9+8-7+6= | | 3x-99= | | 454-35663114672937373372729203997338399=7 | | 454-356631146=468 | | y=cos5x/2 | | y=(cos5x)/2 | | x-2andy=-2x+2 | | 4x+-3+2x=15 | | (7!((5/7)^5)(2/7)^2)/(5!2!) | | 0.04x+x=200 | | f(x)=6/cos^2x | | 5t/13=25/39 | | 2a-a+b= | | -15t+15+9t=7t-4 | | 5r-10=2k | | y=1/3cos3x | | 5b+2a-3b= | | 3/4:2 | | (50+2x)(30+2x)-1500=425 | | 5/8÷3/4= | | (50+2x)(30+2x)-150=425 | | 5s-7/=7 | | 2/9×7/6 | | 4K+12=2k | | (50+x)(30+x)-150=425 | | a+3a-2a-2b= | | 20logx=32.5 | | 12h-15=9h | | a+5a+b= |

Equations solver categories